Synthesis of prostaglandins III: Efficient and practical synthesis of antisecretory prostaglandin enprostil - Lee, Y.S.; Nam, K.H.; CHUNG, SUN HO; Park, H. (Georg Thieme Verlag, 1994)
An efficient and practical 8-step synthesis of enprostil (1) starting from the lactone 2 has been developed. The propargylic acetate 5 was prepared from the lactol 3 by the reaction with ethynylmagnesium bromide followed by acetylation. Propargylic acetate 5 was converted into enprostil (1) via the introduction of an allene moity by reaction with a Grignard reagent in the presence of a CuI · P(OEt)3 complex.